The Use of Oral Anticoagulation Is Not Associated With a Reduced Risk of Mortality in Patients With COVID-19: A Systematic Review and Meta-Analysis of Cohort Studies - Dai, Meng-Fei; Guo, Si-Tong; Ke, Yi-Jun; Wang, Bao-Yan; Yu, Feng; Xu, Hang; Gu, Zhi-Chun; Ge, Wei-Hong (Frontiers in Pharmacology, 2022)
Abstract Background: Hypercoagulability and thromboembolic events are associated with poor prognosis in the coronavirus disease 2019 (COVID-19) patients. Whether chronic oral anticoagulation (OAC) improves the prognosis is yet controversial. The present study aimed to investigate the association between the chronic OAC and clinical outcomes in COVID‐19 patients. Methods: PubMed, Embase, Web of Science, and the Cochrane Library were comprehensively searched to identify studies that evaluated OAC for COVID-19 until July 24, 2021. Random-effects model meta-analyses were performed to pool the relative risk (RR) and 95% confidence interval (CI) of all-cause mortality and intensive care unit (ICU) admission as primary and secondary outcomes, respectively. According to the type of oral anticoagulants (direct oral anticoagulants (DOACs) or vitamin K antagonists (VKAs)), subgroup and interaction analyses were performed to compare DOACs and VKAs. Meta-regression was performed to explore the potential confounders on all-cause mortality. Results: A total of 12 studies involving 30,646 patients met the inclusion criteria. The results confirmed that chronic OAC did not reduce the risk of all-cause mortality (RR: 0.92; 95% CI 0.82-1.03, P=0.165) or ICU admission (RR: 0.65; 95% CI 0.40-1.04, P=0.073) in patients with COVID-19 compared to those without OAC. The chronic use of DOACs did not reduce the risk of all-cause mortality compared to VKAs (P interaction=0.497) in subgroup and interaction analyses. The meta-regression failed to detect any potential confounding on all-cause mortality. Conclusions: COVID-19 patients with chronic OAC were not associated with a lower risk of all-cause mortality and ICU admission compared to those without OAC, and the results were consistent across DOACs and VKAs subgroups. Registration: PROSPERO CRD42021269764.